The Effectiveness of Palu Mayor Regulation Number 19 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as an Effort to Prevent and Control Covid 19 in Palu City - Ismulail, Andi Muhammad Rifqi; Gobel, Fatmah Afrianty; Arman, Arman; Multazam, Andi Muhammad; Alwi, Muhammad Kidri; Ahri, Reza Aril (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2023)
Background: The Increasing Cases of the Covid 19 Pandemic to Indonesia, As a form of emergency response, the Palu City Government of Central Sulawesi Province stipulated Palu Mayor Regulation number 19 of 2020 concerning the implementation of discipline and law enforcement of health protocols as an effort to prevent and control corona virus disease 2019. The purpose of this study is to Analyze in Depth the Effectiveness of Palu Mayor Regulation Number 19 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as an Effort to Prevent and Control Covid 19 in Palu City based on input, process and output factors. Method: This study used qualitative design, informants came from the Health office, and the people of Palu City. Data collection was conducted through observation, in-depth interviews and document review. The informants in this study were the Head of the Legal Section and the Head of the Health Promotion Section of the Health Office and the community of Palu City, Central Sulawesi Province. Results: BBased on input factors, including socialization and participation, funding, the target of law enforcement of health protocols has run well, then process factors such as the implementation of health protocols and sanctions, monitoring and evaluation, coaching and supervision then output factors such as implementing and complying with health protocols are still not running optimally. Conclusion: Inputs, processes and outputs do not run in accordance with Palu Mayor Regulation Number 19 of 2020 because they are less firm and binding and coercive in the field and there are still communities, both individuals and business actors, who violate rules related to the implementation of discipline and law enforcement of health protocols. The suggestion is to be more assertive and remain consistent in providing education and awareness to the public in implementing health protocols, especially in the city of Palu.